Managing Multicultural Education in Islamic Boarding Schools: A Case Study of Minhajul Haq, Subang, Indonesia - Gilang Tris Rahardi; Najihah Abd Wahid (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
This study aims to describe the implementation of multicultural education management at Pondok Pesantren Minhajul Haq Subang using a qualitative descriptive approach. The research focuses on the four core functions of educational management: planning, organizing, implementation, and evaluation. These aspects are analyzed based on the roles of the Mudir Ma’had (head of the Islamic boarding school), the asatidz/asatidzah (teachers), and the involvement of students' parents. The results of the study indicate that multicultural education planning is carried out systematically by the Mudir Ma’had, integrating universal Islamic values such as inclusivism, tolerance, and mutual respect into the pesantren's vision and the learning curriculum. The organizational process is implemented through a clear and structured division of tasks, although it remains relatively centralized. The implementation of multicultural values is conducted gradually, primarily through their integration into specific subjects and student activities that promote the habituation of tolerant behavior. Evaluation is carried out comprehensively by the Mudir Ma’had, encompassing learning instruments, implementation processes, and changes in students' attitudes. The study found that approximately 70% of the planned programs had been implemented as targeted. These findings indicate that Pondok Pesantren Minhajul Haq has successfully developed a model of multicultural education grounded in contextual Islamic values, making a significant contribution to fostering awareness of diversity and promoting social harmony within the pesantren educational environment.